Figuração dos fatos e compreensão de mundo : a possibilidade da contradição como “fronteira” no espaço lógico - Araújo, André Cardoso de (2017)
If the language in your propositional expression intends to realize a true or false judgment about the world, it is necessary to ask about the legitimacy of this relationship-world language. For Wittgenstein (Tractatus) this relationship is key and through Figuration. The aim is to propose and confirm, within some limits, the following conditional: If the world’ structure "said", in the Tractatus, is too reduced by way of logic representation it will be possible to enlarge the structure of the world from the figuration theory itself? Motivated by this mark and postulating a chance of positive answer is that delineates the General itinerary of this dissertation; so the first two chapters clarify the assumption from which we set out, namely: the structure of world said in the “Tractatus” is too reduced by means of representation. The third and last chapter deals with the possibility of seeking to extend the notion world without scorn the theory of figuration, by introducing the contradiction as a “frontier” in the logical space.